Quantum origin of pre-big-bang collapse from induced matter theory of gravity - Bellini, Mauricio (2012)
We revisit a collapsing pre-big-bang model of the universe to study with detail the non-perturbative quantum dynamics of the dispersal scalar field whose dynamics becomes from the dynamical foliation of test massless scalar field ϕ on a 5D Riemann-flat metric, such that the extra space-like coordinate is noncompact. The important result here obtained is that the evolution of the system, which is described thorough the equation of state has the unique origin in the quantum contributions of the effective 4D scalar field ϕ¯.